Malaysian consumer preferences of hypermarkets in the context of global and local brands - Laraib, Senia (2019)
Purpose: This study aims to research the factor influencing Malaysian consumers to shop at any particular hypermarket, and to investigate whether the preferences change according to local or global brand-name. The factors analyzed are Physical environment, Price, Service Quality, Brand Image, Product quality and attitude towards global brands. A big part of this study uses brand image as the mediator and tries to explain how it effects consumer preferences.